THE ORIENTALIST WORK OF THE CHARLES RIEU - Tajibayeva, Ozoda (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
It is well known that the collections of European countries contain numerous rare and invaluable sources of Eastern literature. These rare sources, many of which are lost under various circumstances, formed the basis for the development of Oriental studies abroad. Each of the foreign scholars who studied the sources of Turkic literature made substantial and lasting contribution to the development of this field. The description and scholarly study of the sources of Alisher Navoi’s works, which are most extensively represented in these collections, were first carried out by prominent French, German, British, and Russian scholars. The sources of Turkic literature in Great Britain and the history of their study also constitute an independent and insufficiently explored research area.. Particularly noteworthy is the scholarly work of the English scholar Charles Riou, who introduced the world to the sources of Persian and Turkic literature in the nineteenth century. This scholar made a pioneering contribution contribution to familiarizing the peoples of Europe with medieval Eastern literature and history by systematically cataloguing and interpretingthe sources of the British Museum. Today, almost every researcher working with sources in the field of Oriental studies and Turkology refers to this scholar’s descriptions. In particular, his detailed, methodologically grounded, and philologically precise descriptions of rare sources create significant scholarly convenience for researchers. This article presents information about the scholarly work of the English Orientalist Charles Riou and offers an analytical overview of his contribution to source studies. It identifies the principles he used when describing Persian and Turkic literary sources and clarifies the methodological foundations of his descriptive approach. It demonstrates that his approaches and analytical insights reflections in his descriptions resonate with contemporary scholarly discussions. The significance of both catalogues authored by the scholar for modern scholarship is critically substantiated